Acute Kidney Injury: Causes, Laboratory Findings and Impact of Conservative Management on its Outcome (Medical Forum Monthly, 2020)
Objective: To know the major causes, changes in laboratory findings and impact of conservative treatment on outcome in patients with AKI.Study Design: Retrospective studyPlace and Duration of Study: This study was conducted at the High Dependency Unit (HDU) of Paediatric B Ward, Ayub Teaching Hospital, Abbottabad from January, 2018 to December, 2019.Materials and Methods: Young children of both gender and age between 1 month to 2 year diagnosed with AKI were included while patients with other and chronic co-morbid were excluded. A predesigned proforma was used to extract the data regarding demographics, investigations, diagnosis, and outcome. Data was analyzed using SPSS v.20.0.Results: In total of 50 patients the means age of the sample was recorded as 6.82 ± 5.95 years, in which 29 (58%) were males and 21 (42%) were females. The serum creatinine of had a mean value of 2.06 ± 1.23 mg/dl, while blood urea recorded a mean of 137.75 ± 62.80 mg/dl. Majority 45 (90%) of patients were admitted with diagnosis of septicemia leading to AKI. In total, 30(60%) patients got discharged, 18(36%) patients expired and 2(4%) patients were referred to other centers.Conclusion: Septicemia is leading cause of AKI in young children and high mortality was recorded for conservative management.